A generalization of the G-transformation and the related algorithms - Brezinski, Claude; He, Yi; Hu, Xing-Biao; Sun, Jian-Qing (Applied numerical mathematics, 2010)
In this paper, a generalization of the G-transformation is proposed together with the corresponding auxiliary rs-algorithm for implementation. We show that the related generalization of the rs-algorithm is equivalent to a generalized qd-algorithm. Applications of the generalization of the G-transformation to the computation of infinite integrals are also given.